2009
DOI: 10.1017/s1481803500011246
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported priorities and resources of academic emergency physicians for the maintenance of clinical competence: a pilot study

Abstract: Objectives: Medical licensing bodies and professional colleges require their members to maintain a broad spectrum of knowledge, skills and attitudes, which, when taken together, define a competent emergency physician (EP). The objectives of this pilot study were: 1) to determine the resources used by academic EPs to maintain competence and 2) to determine academic EPs' learning priorities. Methods: Using a modified Dillman method, we surveyed EPs from 2 Canadian academic tertiary health sciences centres. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A comprehensive learning needs analysis of Australasian emergency physicians highlighted that day‐to‐day departmental management and administration might be a source of considerable frustration, and was identified as a highly desirable topic for continuing medical education . A survey of Canadian emergency physicians also demonstrated a need for education in aspects of the Manager role, including patient flow strategies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive learning needs analysis of Australasian emergency physicians highlighted that day‐to‐day departmental management and administration might be a source of considerable frustration, and was identified as a highly desirable topic for continuing medical education . A survey of Canadian emergency physicians also demonstrated a need for education in aspects of the Manager role, including patient flow strategies …”
Section: Discussionmentioning
confidence: 99%
“…19 A survey of Canadian emergency physicians also demonstrated a need for education in aspects of the Manager role, including patient flow strategies. 20 There is an increasing recognition by academic bodies of the need to explicitly address this aspect of training. The UK college of emergency medicine provides detailed outlines of competencies for 'time management and decision making', 'decision making and clinical reasoning', 'team working and patient safety' and 'communication with colleagues and cooperation'.…”
Section: Thementioning
confidence: 99%
“… 22 Another study of academic emergency physicians showed health advocacy was not a priority for professional development. 23 This reduced priority is of paramount importance as it sheds some light on the issues being encountered by learners in this area. If faculty members are adamant that understanding and teaching advocacy is a challenge but improving instruction in this field is not a priority it creates a real problem for education surrounding the Health Advocate role.…”
Section: Methodsmentioning
confidence: 99%
“…They are often the initial point of contact for patients entering the hospital system and are at an advantage to identify and act on the social, environmental, and biologic factors that influence the health of individuals and society. 11 It is important to measure clinical competence in EM residents to ensure that resident training program curricula are providing material and encounters for all aspects of clinical care. Although there has been research on the strengths and weaknesses of the different types of assessment tools, 12 at present, there is no literature on how Canadian residency programs effectively teach and assess their residents' clinical competencies in EM across all seven domains.…”
Section: Competency-based Medical Education In Emergency Medicinementioning
confidence: 99%